Aspectos epidemiológicos das infecções de sítio cirúrgico em cirurgias ortopédicas com implante em um hospital de reabilitação - Aline Rodrigues de Abreu Miranda (2017)
This study is a historical cohort with information from 517 patients submitted to orthopedic surgery with implantation of the SARAH Network of Rehabilitation Hospitals, Brasília unit, from January 2010 to July 2015. Its general objective was to analyze the epidemiological aspects of infections of surgical site in orthopedic surgeries with implant. As a specific objective, it was intended to estimate the global incidence of infection, to estimate the incidence of infection by topography, by type of surgery, according to ASA and potential for wound infection, to identify possible risk factors for infection, to identify microorganisms Responsible for the infection and to propose a model of risk prediction with the studied variables. To reach the proposed objectives, data were analyzed descriptively through simple frequency and measures of central tendency as median mean and standard deviation variability. A GEE logistic regression model was then performed to verify the possible risk factors associated with surgical site infection. The population was characterized by female patients, with a mean age of 58 years and being overweight (BMI> 25kg / m²). Twenty-two ISCs were diagnosed, with a global incidence of 3.5% [95% CI 2.1-5.5]. The superficial infections were the most incidental (1.4%) and among the surgical procedures, hip arthroplasties had the highest rate of infection (4.2%). The incidence of infection in patients classified as ASA III and IV (6.9%) was higher than those classified as ASA I and II (2.6%) and the incidence of infection in clean surgeries was 2.6%. That in potentially contaminated and contaminated surgeries was 15.6%. S. aureus was the most prevalent microorganism. The final adjustment model defined as factors for implant orthopedic surgical infections: the total time of hospital stay, the number of blood transfusions and the potential for contamination of the surgical wound. Conclusion: the incidence was lower than national studies in orthopedic surgeries with implants. The identification of the actual incidence and associated risk factors may support safe surgery programs.